A novel method for sexing live adult Alphitobius diaperinus. Issue 5 (3rd April 2020) - Arena, Julieta Soledad; Defagó, María Teresa
Abstract: This work aimed to identify discriminant morphological characteristics in Alphitobius diaperinus Panzer (Coleoptera: Tenebrionidae) adults that enable live males and females to be distinguished. The method of sexing proposed here is based on dimorphism of the 8th abdominal sternite and is 100% accurate. The method allows differentiation of the sexes non‐destructively. Abstract : This work aimed to identify discriminant morphological characteristics in Alphitobius diaperinus (Coleoptera: Tenebrionidae) adults that enable live males and females to be distinguished. The method of sexing proposed here is based on dimorphism of the 8th abdominal sternite and is 100% accurate. The method allows differentiation of the sexes non‐destructively.